IMPACT OF INDUSTRIAL POLLUTANTS ON CARBOHYDRATE METABOLISM IN CHANNA PUNCTATUS (BLOCH) - BHATTACHARYA, T.; ROY, S. N. (Journal of the Inland Fisheries Society of India, 2021)
The freshwater air-breathing fish Channa punctatus was exposed to sub-lethal concentration of mercuric chloride, cadmium chloride, phenol, ammonia and mixture of these four for 48 hours to determine the short-term effects of these industrial pollutants on carbohydrate metabolism. Fishes were found to be hyperglycemic with a concomitant depletion in the hepatic glycogen content and increase in glucose-6-phosphatase activity on 1st and 2nd day of exposure to single and mixture of pollutants. The results clearly indicate that hepatic glycogen is a major source of hyperglycemia in C. punctatus. Both gluconeogenesis and glycogenolysis result in the formation of glucose-6-phosphate, which is hydrolyzed by glucose-6-phosphatase, found in liver and kidney, before being liberated as glucose into the circulation. Histopthological changes in the hepatopancreas of C. punctatus induced by the pollutants include degeneration of hepatocytes accompanied by karyolysis, apoptosis and necrosis, clumping of cytoplasmic materials, derangement of the pancreatic acini and coagulation of blood in the sinusoids. Renal kidney exhibited tubular degeneration and changes in the corpuscles such as shrinkage of capillaries in the glomeruli and increase in Bowman’s space. It is inferred that industrial pollutants effects the normal hepatic and renal functions of C. punctatus.Key words: Channa punctatus, industrial-pollutants, hepatic glycogen, glucose-6-phosphatase, glomeruli, Bowman’s space